Early prediction of functional prognosis in neurofibromatosis type 2 patients based on genotype–phenotype correlation with targeted deep sequencing - Yu Teranishi; Satoru Miyawaki; Hirofumi Nakatomi; Kenta Ohara; Hiroki Hongo; Shogo Dofuku; Atsushi Okano; Shunsaku Takayanagi; Takahiro Ota; Jun Yoshimura; Wei Qu; Jun Mitsui; et al. (Scientific Reports, 2022)
Abstract Regardless of treatment, the clinical progression of neurofibromatosis type 2 (NF2), particularly in terms of hearing, swallowing, and gait, tend to worsen throughout the patients’ lives. We performed a retrospective analysis of functional outcomes in Japanese NF2 patients to predict their functional prognosis. We analyzed genotype–phenotype correlation based on genetic data from a cohort of 57 patients with a mean follow-up of 14.5 ± 6.0 years. Their functional outcomes, including hearing, swallowing, and ambulation, were reviewed. Performing a targeted deep sequencing, germline NF2 mutations were identified in 28 patients (49.1%), and mosaic NF2 was identified in 20 patients (20, 35.0%). The functional preservation period and outcome differed significantly depending on clinical/genetic factors. Among these factors, “Truncating”, “Mosaic”, and “Age of symptom onset ≥ 25” had the most significant effects on functional disability. By applying a combination of an NF2 mutation type/location, and age of symptom onset, we classified different degrees of functional preservation and progression, schwannoma growth rate and total interventions per year per patient. The prediction of detailed functional outcomes in NF2 patients can plan better strategies for life-long disease management and social integration.